Storytelling with Islamic Values: Shaping Early Language and Faith—or Just Another Story? - Ristawati; Anida; Rita Zahra; Muhammad Iqbal; Shiti Maghfira (Seulanga : Jurnal Pendidikan Anak, 2026)
Storytelling has been recognized as an effective method for early childhood learning, particularly in developing language skills and instilling moral and religious values. However, the extent to which storytelling infused with Islamic values differs from conventional storytelling in shaping early childhood outcomes remains underexplored. The purpose of this research is to critically examine the effectiveness of Islamic storytelling compared to conventional storytelling in influencing early childhood language abilities and inducing foundational religious comprehension. A quantitative approach with a quasi-experimental design was employed, involving 60 children aged 5–6 years from two kindergartens. The experimental group received Islamic storytelling interventions over eight sessions, while the control group engaged in conventional storytelling. Data were collected through pre-test and post-test assessments measuring receptive and expressive language skills, as well as basic understanding of Islamic values. Data analysis techniques included paired sample t-tests and independent sample t-tests to compare mean score differences within and between groups. The results indicate that while both groups showed improvement, the experimental group demonstrated significantly higher gains in both language development and religious understanding compared to the control group. These findings suggest that Islamic storytelling offers distinct advantages beyond those of conventional storytelling, particularly in integrating cognitive-linguistic growth with spiritual formation. This study contributes a critical perspective on the added value of value-based storytelling in early childhood education and offers practical implications for educators seeking to optimize learning media that align with both developmental and religious goals.